Paleomagnetism and age of the Aston dykes and Savage Point sills of the Boothia Uplift, Canada - Jones, D. L.; Fahrig, W. F. (Canadian Journal of Earth Sciences, 1978)
Oriented samples (107) have been drilled for paleomagnetic studies from diabase sills and dykes on either side of the Boothia Uplift, Canada. Six sites at Savage Point are in sills which intrude the Aston Formation; three, at Whitehead Point, north of Savage Point on the east coast of Prince of Wales Island, are in sills which also intrude these strata. Six sites in the Aston Bay area of Somerset Island are in dykes and a sill which cut the Aston Formation; the former also intrude the Hunting Formation. No meaningful results were obtained from the Whitehead Point samples. Paleomagnetic measurements on the Savage Point samples, together with new K–Ar data, strongly suggest these sills belong to the Mackenzie igneous episode (ca. 1240 Ma). The sill in the Aston Bay area apparently belongs to this episode too, whereas most of the dykes are Franklin dykes (ca. 675 Ma). One large dyke was possibly emplaced in Tertiary times. Thus the Aston Formation is older than 1240 Ma and the Hunting Formation is bracketed between 1240 and 675 Ma.